MEDICAL ASSESSMENT OF ARTERIAL HYPERTENSION SEVERITY AND ITS ASSOCIATION WITH SEEKING URGENT MEDICAL ASSISTANCE: ATHENA STUDY RESULTS - M. G. Glezer; R. T. Saygitov (Российский кардиологический журнал, 2009)
The study investigated the medical assessment of arterial hypertension (AH) severity and its association with seeking urgent medical assistance (ambulance calls and hospitalizations). The main criteria for medical assessment of AH severity were the patients’ self-evaluation of their status, systolic blood pressure level, and self-assessment of the pre-administered AH therapy effectiveness. The prognostic value of medical assessment of AH severity was relatively low, with sensitivity of 51% and specificity of 74% for visual analogue scale (VAS) assessment (≥55 points). The more accurate instrument for assessing the risk of seeking urgent medical assistance was the SCORE risk scale (risk level ≥2,4%). Patients’ self-assessment of their status with VAS had additional prognostic value. All three methods combined could result in sensitivity of 90%, but specificity of 34%. The doctors linked their assessment of AH severity with a necessity to use more antihypertensive medications in more severe patients. However, among patients with medically assessed severity ≥55 VAS points, adding indapamide retard to the therapy resulted in a significant reduction in the risk of seeking urgent medical assistance (odds ratio 0,36; 95% confidence interval 0,20-0,73). No such effect was observed in medically assessed “non-severe” patients.